2019
DOI: 10.1152/ajplung.00521.2018
|View full text |Cite
|
Sign up to set email alerts
|

Consumptive coagulopathy is associated with organ dysfunction during PICS

Abstract: Patients who survive the acute phase of sepsis can progress to persistent inflammation, immunosuppression, and catabolism syndrome (PICS). Although sepsis is characterized by early hypercoagulability and delayed hypocoagulability, coagulopathy during chronic critical illness is not fully understood. The objective of this study was to determine whether sepsis-induced PICS is associated with coagulation abnormalities. Using our previously described murine PICS model, outbred mice underwent cecal ligation and pun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Although the activation of coagulation is protective to counteract pathogens through fibrin deposition [ 20 ], excessive coagulopathy can be expected to accelerate inflammation [ 8 ] and to worsen microcirculation, possibly leading to multiple organ failure [ 7 ]. Reportedly, extreme coagulopathy has been observed in the blood and organs in PIICS model mice [ 21 ]. Based on results of the present study, decreased antithrombin activity was identified as a risk factor for PIICS.…”
Section: Discussionmentioning
confidence: 99%
“…Although the activation of coagulation is protective to counteract pathogens through fibrin deposition [ 20 ], excessive coagulopathy can be expected to accelerate inflammation [ 8 ] and to worsen microcirculation, possibly leading to multiple organ failure [ 7 ]. Reportedly, extreme coagulopathy has been observed in the blood and organs in PIICS model mice [ 21 ]. Based on results of the present study, decreased antithrombin activity was identified as a risk factor for PIICS.…”
Section: Discussionmentioning
confidence: 99%
“…"Persistent Inflammation, Immunosuppression, and Catabolism Syndrome" (PICS) has been postulated as the underlying pathophysiology of chronic critical illness (CCI) (18,47). About 50% of sepsis patients have a debilitating condition characterized by a self-perpetuating cycle of persistent low-grade systemic inflammation mimicking chronic stress (elevated cortisol) (44,48,49), glucocorticoid resistance, altered hemostasis (50,51), mitochondrial dysfunction (52,53), and accelerated inflamm-aging (9,54), with increased risk for chronic inflammatory systemic diseases (7,55). The evolutionary trade-off between acutely beneficial and chronically harmful homeostatic corrections was the subject of a recent review (7).…”
Section: Innate Immunity and Nuclear Factor-κbmentioning
confidence: 99%
“…Cecal ligation and puncture was performed on 6 to 8-weekold male CD-1 mice from the Charles River Laboratories (Wilmington, MA, USA) as described previously (15). The animal protocol was approved under the Institutional Animal Care and Use Committee of the University of Cincinnati (Protocol No.…”
Section: Cecal Ligation and Puncture Modelmentioning
confidence: 99%